KONSEP DIRI REMAJA PUTRI OBESITAS - Windy Claudia; T.Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Adolescence is the arrival of puberty transition from childhood to adulthood. This period is almost always a difficult time for teenagers. Adolescence is a phase of development of the individual segments are very important, beginning with the physical maturation of the organs. The physical changes are common in adolescents are obese. Obesity is excess weight due to excessive accumulation of body fat. The physical appearance of the desire to have an ideal body is highly desirable for women particularly among adolescent girls because at this time people began to interact with the social environment and also the opposite sex ideal body among adolescents is considered something that has an appeal but not with adolescents who are obese. This led to the concept of self in young women who are obese may be disrupted, less or not in accordance with his problems. The purpose of this study was to determine the characteristics of young, self-concept, and the causes of obesity in adolescent girls. This study uses qualitative research collection techniques informants Accidental in Pekanbaru City High School. Number of research informant as much as 5 people. Measuring instrument used in this study interview guides and documentation. The results showed that the characteristics of teenage obesity has pekerjaaan parents who established that as a civil servant, is generally self-concept of young women has a negative self concept, and the causes of obesity in adolescent girls are heredity, environmental factors lifestyle and lack of activity sport. It is suggested in adolescents who are obese are fostering her ability to channel the talents and hobbies like sports or singing owned and other achievements.Keywords: Obesity, self-concept, teenager